Linguocultural significance of phraseological units representing the concepts of time and space in English and Uzbek languages - Ishonkulov, Sherzod Usmonovich (The Lingua Spectrum, 2026)
This article investigates the comparative linguocultural characteristics of phraseological units (PUs) representing the fundamental categories of “Time” and “Space” in the English and Uzbek languages. By examining the metaphorical and metonymic foundations of these idioms, the research demonstrates how historical, geographical, and social factors shape the linguistic world-view of each culture. The study identifies common cognitive models, as well as language-specific nuances, that reflect the unique cultural codes of English and Uzbek speakers. Time and space are the primary coordinates of human existence; in linguistics, these concepts are not merely physical dimensions but are perceived through the prism of culture. Phraseological units are rich in cultural memory, serving as unique vessels that preserve a nation’s history and values. Although English and Uzbek belong to different language families such as Germanic and Turkic, respectively both make extensive use of idioms to express the complex aspects of chronology and topography. This research aims to analyze how these two cultures linguistically internalize and harmonize abstract concepts such as time and space.